Not Only Language Awareness but also Cultural Awareness Required in Teaching English as a Global Language - Indawan Syahri (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
Language use involves not only making choices about lexis, grammar, discourse structures and other language aspects, but also contexts, i.e. topics, participants, settings. The explicit knowledge, sensitivity, and perception on the language regularities, so-called language awareness is essential for the language users to understand and produce language accurately. Learners are also expected to recognize language users’ norms, belief systems and behaviors. Cultural awareness, as the knowledge of cultural differences among the first language cultures and others speakers’ cultures, is of paramount. Since the number of ‘new variants’ of English from periphery countries are increasing (Canagarajah 2002) and at the same time English has become ‘de-nationalized’ (McKay 2002) other speakers’ culture--the writer means--are cultures of inner-cycle (native) speakers, outer-cycle (L2) speakers, and extended-cycle (FL) speakers (see Kachru 1985). Intercultural awareness is vitally taught to English learners as the response to global English.